Research as praxis, en route theory/practice teacher-researcher collaboration: a self-study - Gade, Sharada (NOMAD Nordic Studies in Mathematics Education, 2017)
This paper relates to project related instructional interventions, conducted via teacher-researcher collaboration in a Grade Four mathematics classroom. Drawing upon cultural historical activity theory or CHAT perspectives, such conduct exemplifies research as praxis. While CHAT perspectives argue for a theory/practice approach, enabling practitioners to act on their reflexivity and address contradictions found in ongoing practice; research as praxis views practitioner reflexivity as central to pursuing openly ideological work and practising in empirical inquiry what one preaches in theoretical formulations. Such pursuit led to our becoming stakeholders in each other’s professional practice and the conduct of interventions becoming the shared object of both teaching and research. In teacher-researcher collaboration realising expansive learning activity, it was possible to question modernist assumptions which view abstract theory as applicable to any concrete practice and take political action in dialectic with theory.